ON THE REASONS FOR THE EMERGENCE OF THE KHAZAR CITY IN THE VOLGA DELTA - Dmitry V. Vasiliev (Археология евразийских степей, 2024)
The article presents the author's insight on the reasons for the emergence of the city in the Volga delta in Khazar period. The main reason is declared the necessity of transshipment of goods from sea ships to river boats during trade along the Caspian-Volga trade route. The changes in the routes of movement of goods along the Volga route in the VIII–IX centuries (by passing the Volga delta) and in the X century (via the Volga delta) due to a change of starting point of these routes – Damascus in the early period and Baghdad in the late period, are traced. The second reason for the emergence of the city in the Volga delta is the presence here of the nomadic headquarters of the Khazar Khagans, whose name in Russian sounds like “Belaya” (White). Associating this name with the color designation of the cardinal points in Turkic culture, the author suggests that initially the “White” or Western headquarters as the center of Khazaria corresponded to the Western headquarters of the Turkic Kaganate. Thus, the political continuity of Khazaria in relation to the Turkic Kaganate is declared. It is suggested that the original location of the “White” headquarters corresponds to the vicinities of the village of Semibugry in the central part of the Volga delta, and its transformation into a full-fledged city can be traced archaeologically at the Samosdelka settlement in the western part of the delta, where it was moved in the X century as a result of the Caspian transgression.